RISK TO POPULATION HEALTH DURING RECLAMATION OF LANDS DISTURBED IN COAL MINING - Кислицына, Вера Викторовна; Суржиков, Дмитрий Вячеславович; Голиков, Роман Анатольевич; Ликонцева, Юлия Сергеевна (Medicine in Kuzbass, 2024)
The study aim was to assess the health risk to the population exposed to atmospheric emissions during reclamation work at a liquidated coal mine. Materials and methods. The study was conducted at the industrial site of Sibenergougol LLC, located in the Kuibyshevsky district of Novokuznetsk. The volume of maximum permissible emissions of the enterprise was used as a source of initial data. Calculations of maximum single and average daily concentrations of pollutants in 30 calculation points were performed using the ECOcenter-Standard software package according to the «Methods for calculating the dispersion of emissions of harmful (polluting) substances in the atmospheric air». Maximum permissible concentrations of substances were determined in accordance with the Sanitary rules and norms 1.2.3.3685-21. The calculation of carcinogenic risk and hazard indices was performed using the Guideline 2.1.10.1920-04. Results. Nitrogen dioxide, nitrogen oxide, carbon monoxide, sulfur dioxide, carbon (soot), inorganic dust with SiO2 content of 20-70»% were selected for non-carcinogenic risk assessment. Carcinogenic risk assessment was performed from the exposure to carbon (soot). Maximum concentrations of pollutants are in the range from 2×10-6 (inorganic dust with SiO2 content of 20-70»%) to 0.170 mg/m3 (carbon monoxide). Average concentrations are in the range from 1×10-7 (inorganic dust with SiO2 content of 20-70»%) to 0.014 mg/m3 (carbon monoxide). No excess of maximum permissible concentrations of the substances was detected. The highest concentrations of the substances and, accordingly, the highest hazard indices are observed at the points located in the settlement of Listvyagi, which is due to the closeness of the sources of atmospheric emissions. At the same time, the hazard coefficients for acute and chronic inhalation effects for all substances do not exceed one, which is acceptable. It was found that the greatest impact is on the respiratory system. The carcinogenic risk due to the exposure to carbon (soot) is within the range of 1×10-6 to 5×10-7, which does not exceed the acceptable level. Conclusion. Atmospheric emissions from the mine reclamation site have some impact on the health of residents of the Listvyagi settlement, where the highest hazard indices have been identified.